Effect of Adopting the New Race-Free 2021 Chronic Kidney Disease Epidemiology Collaboration Estimated Glomerular Filtration Rate Creatinine Equation on Racial Differences in Kidney Disease Progression Among People With Human Immunodeficiency Virus: An Observational Study. (7th September 2022) - Muiru, Anthony N; Madden, Erin; Scherzer, Rebecca; Horberg, Michael A; Silverberg, Michael J; Klein, Marina B; Mayor, Angel M; John Gill, M; Napravnik, Sonia; Crane, Heidi M; Marconi, Vincent C; Koethe, John R; et al.
Abstract: Background: The impact of adopting a race-free estimated glomerular filtration rate (eGFR) creatinine (eGFRcr) equation on racial differences in chronic kidney disease (CKD) progression among people with human immunodeficiency virus (PWH) is unknown. Methods: We defined eGFR stages using the original race-adjusted Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) eGFRcr equation and the new race-free CKD-EPI eGFRcr equation. We then estimated 5-year probabilities of transitioning from baseline kidney function to more advanced eGFR stages and examined the association of race (black vs white) with rates of CKD progression using Markov models. Results: With the race-adjusted eGFRcr equation, black participants (n = 31 298) had a lower risk of progressing from eGFR stage 1 to 2 (hazard ratio [HR], 0.77; 95% confidence interval [CI], .73–.82), an equal risk of progressing from stage 2 to 3 (1.00; .92–.07) and a 3-fold risk of progressing from stage 3 to 4 or 5 (3.06; 2.60–3.62), compared with white participants (n = 27 542). When we used the race-free eGFRcr equation, 16% of black participants were reclassified into a more severe eGFR stage at baseline. The reclassified black individuals had a higher prevalence of CKD risk factors than black PWH who were not reclassified. With the race-free eGFRcr equation, black participants had a higher risk of disease progression across all eGFR stages than white participants. Conclusions: The original eGFRcr equation systematically masked a subgroup of black PWH who are at high-risk of CKD progression. The new race-free eGFRcr equation unmasks these individuals and may allow for earlier detection and management of CKD. Abstract : Adoption of the new race-free 2021 CKD-EPI eGFR equation identified more Black individuals with HIV as having chronic kidney disease (CKD) and revealed a higher risk of CKD progression. This may allow for earlier detection and management of CKD risk.